Association between pulmonary artery to aorta diameter ratio with pulmonary hypertension and outcomes in diffuse cystic lung diseases. Issue 25 (25th June 2021) - Baldi, Bruno Guedes; Fernandes, Caio Júlio César dos Santos; Heiden, Gláucia Itamaro; Freitas, Carolina Salim Gonçalves; Sobral, Juliana Barbosa; Kairalla, Ronaldo Adib; Carvalho, Carlos Roberto Ribeiro; Souza, Rogério
Abstract : Abstract: To investigate the importance of pulmonary vascular measurements on computed tomography (CT) in predicting pulmonary hypertension (PH) and worse outcomes in diffuse cystic lung diseases (DCLDs). We conducted a cross-sectional study of patients with DCLDs. Patients underwent pulmonary function tests, a six-minute walk test (6MWT), chest CT, transthoracic echocardiography, and right heart catheterization. Pulmonary artery (PA) diameter and PA-ascending aorta ratio (PA-Ao ratio) were obtained from CT. Mean pulmonary artery pressure (mPAP) from right heart catheterization was correlated with tomographic, functional, and echocardiographic variables. The association between the PA-Ao ratio with outcomes was determined by Kaplan–Meier curves. Thirty-four patients were included (18 with pulmonary Langerhans cell histiocytosis and 16 with lymphangioleiomyomatosis, mean age 46 ± 9 years). Forced expiratory volume in the first second and lung diffusing capacity for carbon monoxide were 47 ± 20% and 38 ± 21% predicted, respectively. PA diameter and PA-Ao ratio were 29 ± 6 mm and 0.95 ± 0.24, respectively. PA-Ao ratio > 1 occurred in 38.2% of patients. PA-Ao ratio was a good predictor of PH. mPAP correlated best with PA-Ao ratio, PA diameter, oxygen desaturation during six-minute walk test, and echocardiographic variables. Patients with PA-Ao ratio > 1 had greater mPAP, and a higher risk of death or lung transplantation (log-rank, P  < .001) than those with PA-Ao ratio ⩽ 1. The PA-Ao ratio measured on CT scan has a potential role as a non-invasive tool to predict the presence of PH and as a prognostic parameter in patients with DCLDs. Abstract : Supplemental Digital Content is available in the text